Striking the balance: Unveiling the interplay between photocatalytic efficiency and toxicity of La-incorporated Ag3PO4 - Ribeiro, Lara K.; Assis, Marcelo; Moreira, Ailton J. [UNESP]; Abreu, Cínthia B.; Gebara, Renan C.; Grasser, Giovanna A.; Fukushima, Hirla C.S.; Borra, Ricardo C.; Melão, Maria G.G.; Longo, Elson; Mascaro, Lucia H. (Elsevier, 2024)
Persistent molecules, such as pesticides, herbicides, and pharmaceuticals, pose significant threats to both the environment and human health. Advancements in developing efficient photocatalysts for degrading these substances can play a fundamental role in remediating contaminated environments, thereby enhancing safety for all forms of life. This study investigates the enhancement of photocatalytic efficiency achieved by incorporating La3+ into Ag3PO4, using the co-precipitation method in an aqueous medium. These materials were utilized in the photocatalytic degradation of Rhodamine B (RhB) and Ciprofloxacin (CIP) under visible light irradiation, with monitoring conducted through high-performance liquid chromatography (HPLC). The synthesized materials exhibited improved stability and photodegradation levels for RhB. Particularly noteworthy was the 2% La3+-incorporated sample (APL2), which achieved a 32.6% mineralization of CIP, nearly three times higher than pure Ag3PO4. Toxicological analysis of the residue from CIP photodegradation using the microalga Raphidocelis subcapitata revealed high toxicity due to the leaching of Ag + ions from the catalyst. This underscores the necessity for cautious wastewater disposal after using the photocatalyst. The toxicity of the APL2 photocatalysts was thoroughly assessed through comprehensive toxicological tests involving embryo development in Danio rerio, revealing its potential to induce death and malformations in zebrafish embryos, even at low concentrations. This emphasizes the importance of meticulous management. Essentially, this study adeptly delineated a thorough toxicological profile intricately intertwined with the photocatalytic efficacy of newly developed catalysts and the resultant waste produced, prompting deliberations on the disposal of degraded materials post-exposure to photocatalysts.
Keywords: Ciprofloxacin; Ecotoxicology; Organic pollutants; Silver orthophosphate